PIK3CA Mutations and Neoadjuvant Therapy Outcome in Patients with Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer: A Sequential Analysis - Seo, Youjeong; Park, Yeon Hee; Ahn, Jin Seok; Im, Young-Hyuck; Nam, Seok Jin; Cho, Soo Youn; Cho, Eun Yoon (Journal of breast cancer, 2018)
mutation is considered to be a possible cause for resistance to neoadjuvant chemotherapy (NAC) in human epidermal growth factor receptor 2 (HER2)-positive breast cancer. We investigated the association between mutations and the outcome of NAC in HER2-positive breast cancers. A total of 100 HER2-positive breast cancer patients who had undergone NAC and surgery between 2004 and 2016 were examined. Mutation status was sequentially assessed in pre-NAC, post-NAC, and recurrent specimens taken from these patients. mutations were identified in the sequential specimens of 17 patients (17.0%). These 17 patients experienced shorter disease-free survival (DFS) than the rest of the patients (58.3 months vs. 119.3 months, =0.020); however, there was no significant difference in pathologic complete response (pCR) and overall survival (OS) (pCR, 17.6% vs. 33.7%, =0.191; OS, 84.5 months vs. 118.0 months, =0.984). While there was no difference in pCR between the wild-type and mutant groups in pre-NAC specimens (25.0% vs. 31.8%, =0.199), mutations correlated with lower pCR in post-NAC specimens (0.0% vs. 24.3%, <0.001). Multivariate analysis revealed significantly worse DFS in the mutant group than in the wild-type group (hazard ratio, 3.540; 95% confidence interval, 1.001-12.589; =0.050). Moreover, the DFS curves of the change of mutation status in sequential specimens were significantly different ( =0.016). mutation in HER2-positive breast cancer was correlated with a lower pCR rate and shorter DFS. These results suggest that mutation is a prognostic marker for NAC in HER2-positive breast cancer, especially in post-NAC specimens.